PROPHETIC LEADERSHIP DALAM PENGEMBANGAN KARIR KARYAWAN DI WAROENG GROUP - Fitriana, Nita (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2020)
Waroeng Group is a company established by a couple of Jhody-Anik. This company is culinary business. This company is different from others in its vision. The vision is Spiritual Company concept. It is based on Islamic values. It means that the leadership model is also based on Islamic values namely prophetic leadership. This research aimed to describe how the prophetic leadership model effects career development of Waroeng Group employee. This study used qualitative research combining between literature review and field research at Waroeng Group. The result explained that 1). Prophetic leadership values; Shiddiq, Amanah, Tabligh and Fathonah gave significant effect in career development of Waroeng Group employee, 2). Prophetic leadership values can be seen in two things; first, in training and education process, second in promotion and mutation process of Waroeng Group employee. By implementing prophetic leadership in career development of Waroeng Group employee, it is expected that the employee do not only develop the company but also their career.